Roots from mulberries (Morus alba) natural and hybrids varieties: phenolic contend and nutraceutical potential as antioxidant - Denise Sande, Maykelis Díaz Solares, Yanio Enrique Milián Rodríguez, Inelvis Castro Cabrera, Leydi Fonte Carballo, Nancy Altunaga Pérezb, Yudit Lugo Moralesb, Gecernir Colenc, Jacqueline Aparecida Takahashia (Journal of Applied Pharmaceutical Science, 2016)
Fruits of Morus alba have been described as source of phytochemicals with antioxidant activity, which is of interest for human consume, and food industry. However, differences in antioxidant capacity among varieties of this species, as well as the potential of other parts of this plant has been little explored. In this work, extracts of roots from twelve (natural or hybrid) varieties of M. alba were evaluated. There were observed differences between varieties, as the range of total phenol content among hexane, ethanol and aqueous extracts (0.55 – 1.59; 2.72 – 6.61; 5.09 – 9.85 gallic acid /100 g of extract, respectively). Antioxidant action of M. alba roots extracts was proved in different assays as radical scavenger and iron reduction capacity. Ethanol was found to be the best solvent to extract antioxidant compounds. Among all extracts assayed, the best association between high phenol and flavonoid content associated to free radicals scavenger and iron reducing power activities were shown by ethanol root extract from hybrid variety IZ 64. This work demonstrated that M. alba roots possess great potential as source of phytochemicals with antioxidant activity and pointed variety IZ 64 as the best cultivar to be used due to its functional properties or as source of natural antioxidants.
Keywords: Morus alba varieties, mulberry, root, antioxidant, radical scavenging.